Brasil figuração x abstração no final dos anos 40 - Ferreira, Glória 1947- (IAC, Instituto de Arte Contemporânea, 2013)
This book complements the eponymous exhibition organized by the Instituto de Arte Contemporânea - IAC and sponsored by Itaú cultural, at the Museu de Belas Artes in São Paulo, from November 24, 2011 to February 19, 2012, bringing together 22 texts by art critics and artists from the late 1940s. The book documents an important period in the history of Brazilian art, between the 1930s and 1940s, where there was great debate between figurative and abstractionist artists. These brought to Brazil the artistic style that had predominated in Europe since the beginning of the 20th century. Includes texts by Di Cavalcanti, Luís Martins, Plínio Ribeiro Cardoso, Clóvis Graciano, Samson Flexor, Flávio de Carvalho, Candido Portinari, Waldemar Cordeiro, Sérgio Milliet, Léon Degand, Mario Pedrosa, Antonio Bento, Santa Rosa, Quirino Campofiorito, Lothar Charoux, Ibiapaba de Oliveira Martins, among others
Keywords: Geschichte 1930-1950; Abstrakte Kunst; Brasilien; Aufsatzsammlung; Ausstellungskatalog -- Instituto de Arte Contemporânea -- 24.11.2011-19.02.2012 -- São Paulo